Isolation, social stress, low socioeconomic status and its relationship to immune response in Covid-19 pandemic context - Santos, Rodrigo Mattos dos [UNESP] (Elsevier, 2020)
The coronavirus disease 2019 (COVID-19) outbreak was first reported December 2019, in Wuhan, China, and has since spread worldwide. Social distancing or isolation measures were taken to mitigate the pandemic. Furthermore, stress and low socioeconomic status in humans confer increased vulnerability to morbidity and mortality, what can be biologically observed. This condition tends to remain during the Covid-19 pandemic. Social disruption stress (SDR) raises important questions regarding the functioning of the immune system, and the release of several stress hormones. A molecular pattern, conserved transcriptional response to adversity (CTRA), is thought to have evolved to defend against physical injury during periods of heightened risk. Chronic CTRA activation could leave an organism vulnerable to viral infections, leading to increased pro-inflammatory gene expression and a suppression of anti-viral gene expression. The activation of such transcriptional status is related to conditions of social stress through either hostile human contact, or increased predatory vulnerability due to separation from the social group and also low socioeconomic status. This review aims to point out questions for government officials, researchers and health professionals to better target their actions during a pandemic and encourage studies for a better understanding of these characteristics.
Keywords: Conserved transcriptional response to adversity (CTRA); Covid-19; Immune response; Social disruption stress; Sociogenomics; Stress hormones